Uncertainty, Experience and the “Winner's Curse” in OCS Lease Bidding - Gilley, Otis W.; Karels, Gordon V.; Leone, Robert P. (Management Science, 1986)
This paper presents an empirical test of the major hypothesis of the currently-accepted bidding models in two regions of differing tract value uncertainty. The most significant result is an empirical verification that the more bidders that bid on a particular parcel in the face of great uncertainty, the lower the bid levels of individual firms that participate given all else is constant. No such relationship was observed, however, in the sale where there was previous bidding experience and prior ownership of closely related tracks. Prior models have not been able to identify the inverse relationship because of a bias that occurs when only positive bids are employed in these models and the use of data where previous experience reduces uncertainty. In the analysis of the competitive bidding situation, we use a two-stage procedure which adjusts for this “selection bias” by allowing for the incorporation of information from the dichotomous bid/no-bid decision in the modeling of bid level.